2023
DOI: 10.1021/acs.est.2c07810
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mass Concentration of Microplastics and Nanoplastics in Wastewater Treatment Plants by Pyrolysis Gas Chromatography–Mass Spectrometry

Abstract: The level of microplastics (MPs) in wastewater treatment plants (WWTPs) has been well evaluated by the particle number, while the mass concentration of MPs and especially nanoplastics (NPs) remains unclear. In this study, pyrolysis gas chromatography–mass spectrometry was used to determine the mass concentrations of MPs and NPs with different size ranges (0.01–1, 1–50, and 50–1000 μm) across the whole treatment schemes in two WWTPs. The mass concentrations of total MPs and NPs decreased from 26.23 and 11.28 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…often prevent direct measurement of plastic mass, and converting between abundance and % w/w values requires assumptions about particle size, shape, and polymer type that may not be accurate for heterogeneous mixtures of plastic types. Emerging techniques that result in direct mass measurements, such as gas chromatography–mass spectrometry (GC/MS)-based methods, have drawbacks as well. First, they cannot differentiate between different particle shapes, which would preclude measurement of film plastic content required by some regulations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…often prevent direct measurement of plastic mass, and converting between abundance and % w/w values requires assumptions about particle size, shape, and polymer type that may not be accurate for heterogeneous mixtures of plastic types. Emerging techniques that result in direct mass measurements, such as gas chromatography–mass spectrometry (GC/MS)-based methods, have drawbacks as well. First, they cannot differentiate between different particle shapes, which would preclude measurement of film plastic content required by some regulations.…”
Section: Resultsmentioning
confidence: 99%
“…First, they cannot differentiate between different particle shapes, which would preclude measurement of film plastic content required by some regulations. Second, these methods typically require small sample sizes and may exclude particles >1 mm, 41 which can account for a substantial percentage of plastic mass content (Figure 3b) and will require larger extrapolation factors. The latter is problematic considering the likely heterogeneous distribution of microplastics in materials like those studied here.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although methanol was used in this study to remove any organic matter adhered to the MNPs, and temperatures of 90 °C were used to dry the samples, the authors reported no signi cant effects on the integrity of the MNPs (Y. Xu et al, 2023). In another study, Li et al (2021) employed Pyr-GC/MS to detect and quantify NPs absorbed by the root system of cucumber and stored within the plant.…”
Section: Methodsmentioning
confidence: 92%
“…Similarly, a protocol was recently proposed to quantify microand nanoplastics in wastewaters by synergistically employing sequential micro ltration (1000-50-1 µm) and cross-ow ultra ltration (~10 nm), hydrogen peroxide digestion, and density separation (microplastics) or centrifugal ultra ltration (nanoplastics) (Y. Xu et al, 2023). The authors sampled 25, 50, and 100 L of primary, secondary, and tertiary settler e uents, respectively, using sampling buckets.…”
Section: Methodsmentioning
confidence: 99%
“…Plastic pollution in natural and engineered environments has been a global concern, with an increasing number of microplastics being detected in oceans, lakes, sediments, and wastewater treatment plants (WWTPs). The molecular structure of plastics is inherently robust, allowing them to persist in environments for centuries or even millennia once discarded. , Unfortunately, owing to the small size of microplastics and the lack of specific treatment processes and equipment in WWTPs, it is challenging to remove microplastics from wastewater and sludge effectively . Consequently, the content of microplastics in domestic wastewater, industrial wastewater, and sewage sludge was reported to reach 219–890 particles/L, , 443–2713 particles/L, , and 1000–183 000 particles/kg, respectively .…”
Section: Introductionmentioning
confidence: 99%